Youth labor market in Kazakhstan: problems and solutions - Baidybekova, S.K.; Sauranbay, S.B.; Syzdykova , E.Zh. (BUKETOV BUSINESS REVIEW, 2023)
Object: The main purpose of the study was to reflect the main problems of youth employment in market conditions, as they constitute a promising part of the working-age population of the country and ways to solve them. Methods: When conducting research, various methods and methods were used in the work: induction and deduction, analysis and synthesis, economic and statistical analysis of economic indicators. The object of the study is the youth labor market in Kazakhstan. The subject of the study is the study of youth employment problems, as well as the ways to solve them. Findings: One of the main measures for the development and improvement of the labor market is the constant monitoring of the labor market, in which it is necessary to study the supply and demand in the labor market. The results of the study can be applied in practice when monitoring the employment market of the population, especially young people as the most active part of the population. Conclusions: The problem of youth employment arises not only at the level of one region, but also at the state level due to the peculiarities of this socio-demographic group, for which it is necessary to carry out systematic work to study the supply and demand for labor.